BUDGETING PARTICIPATION SYSTEM (BPS) ON MANAGERIAL PERFORMANCE IN THE DEVELOPMENT OF A THOUSAND HOUSES IN GRESIK CITY - Kusmayati, Nindya Kartika; Wahib, Moh; Prasetyo, Hendra Dwi (STIE Mahardhika, 2020)
BPs can build an environment that may receive timely scope and information by subordinates, and in this environment, decision making can be easy and effective. Thus, subordinates can obtain accuracy of information and scope about overall organization and take the right position to reach the target organization by considering tasks more clearly. this research uses data a questionnaire with this research population is managers and core employees of the 1,000 house construction project in Gresik City. Secondary data for this research base on literature, interviews, and other sources such as books, the internet, and others. SPSS output results show generated regression of the influence of BPs on Managerial Performance. With the meaning increasing BPs, the higher value of Managerial Performance. The results in this study support the research conducted by Saidu et al. (2017), Tanase (2013), and Eker (2009), which stated that BPs had effect on Managerial Performance despite different research objects.